Design Analysis of a Manhole Mining Ambulance with a Hilux 4×4 WD Single-Cabin Chassis Unsing Finite Element Analysis (FEA) - Gunawan, Rezananda; Fuad Hilmy; Ikhwan Taufik (Politeknik Piksi Ganesha Indonesia, 2024)
This study aims to determine the strength and durability of ambulance manhole structures intended for emergency situations in mining areas. The research includes a literature review, direct calculation of manhole dimensions, design development, material selection, and loading simulation using SolidWorks 2021 software. The evaluated parameters are von Mises stress, deformation, and safety factor. Three variations of manhole designs and three types of materials—ASTM A500, Galvanized Steel, and JIS G34445 STKM 13B—are considered. Simulation results are presented in tabular form. The optimal design and material identified is Design 2, which exhibits von Mises stress of 3.759 MPa, deformation of 1.749 mm, and a safety factor of 8.1.